A Hybrid Address Allocation Algorithm for IPv6 - Murugesan, Raja Kumar; Ramadass, Sureswaran (Recent Trends in Network Security and Applications, 2010)
The scalability of the Internet routing system has caught much attention in the recent years as it affects the performance of the Internet greatly. IP address fragmentation is one main cause for routing scalability and existing address allocation practices are one major contributor to address fragmentation. Address fragmentation increases routing table size, hence IP look-up and routing efficiency. It also constraints the processing and memory capabilities of routers leading to failing routes if the burgeoning growth of the routing table size is not contained. A proper address allocation algorithm coupled with appropriate address allocation policies will help to scale the existing addressing and routing system. This research proposes a hybrid address allocation algorithm for IPv6 by combining some of the existing address allocation algorithms leveraging on their merits. The proposed hybrid address allocation algorithm would help in reducing address fragmentation to a greater extent compared to the existing address allocation schemes. This would facilitate in reducing routing table size, increase scalability and hence improve the performance of the Internet.